Constitutional or ethnocultural? National identity as a European legal concept - Kriszta Kovács (Intersections: East European Journal of Society and Politics, 2022)
Identity has long been a contested concept in the social sciences. In contrast, legal scholars have come late to the analytical discussion about the concept. It was only in the late 2000s that the concepts of national and constitutional identity became part of the European legal discourse. Today, national identity is a legal concept in EU law. Article 4(2) of the Treaty on European Union obliges the EU to respect the national identities of Member States. A literal understanding of this provision suggests that any domestic interpretation would be consistent with EU law. This paper challenges this view. It differentiates between national and constitutional identity. The former refers to identity that can be connected either to a community's ethnocultural characteristics or to its political institutions and foundational constitutional values. The latter is often called constitutional identity. Yet, this article defines the term constitutional identity differently by concentrating on identity attached to a democratic constitution. Thereby, it offers a novel, constitutionalist approach. The article argues that the concept of national identity in EU law is a constitutionalist one and demonstrates, using the example of Hungary, how an ethnocultural national identity runs counter to this constitutionalist concept and how a new constitutional identity may be developed. The implication of having a constitutional identity that respects universal constitutional principles is that such a constitutional identity would be more compatible with values at the European level.
Keywords: 330; constitutional identity; national identity; ethnocultural justification; European Union; Hungary